2014
DOI: 10.1021/nn503755c
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Integrated Strength and Toughness Artificial Nacre Based on Dopamine Cross-Linked Graphene Oxide

Abstract: Demands of the strong integrated materials have substantially increased across various industries. Inspired by the relationship of excellent integration of mechanical properties and hierarchical nano/microscale structure of the natural nacre, we have developed a strategy for fabricating the strong integrated artificial nacre based on graphene oxide (GO) sheets by dopamine cross-linking via evaporation-induced assembly process. The tensile strength and toughness simultaneously show 1.5 and 2 times higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
304
4
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 364 publications
(331 citation statements)
references
References 37 publications
21
304
4
2
Order By: Relevance
“…Recent studies reported that the dopamine could self‐polymerize to form surface‐adherent polydopamine (PDA) films onto a wide range of materials either organic or inorganic by a spontaneous oxidation reaction in an alkaline solution (pH = 8.5) 18, 19, 20, 21. It was widely used as material surface modification since the PDA shells are stable enough to reach the target cells after intravenous injection 22, 23.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that the dopamine could self‐polymerize to form surface‐adherent polydopamine (PDA) films onto a wide range of materials either organic or inorganic by a spontaneous oxidation reaction in an alkaline solution (pH = 8.5) 18, 19, 20, 21. It was widely used as material surface modification since the PDA shells are stable enough to reach the target cells after intravenous injection 22, 23.…”
Section: Introductionmentioning
confidence: 99%
“…This unique existence of multiple interface interactions and building blocks in natural materials inspires constructing different synergistic effects in bioinspired nanocomposites. For example, Cui et al [86] demonstrated synergistic interface interactions of hydrogen and covalent bonding in GO-based nanocomposites. The dopamines could not only be grafted to GO nanosheets, but also self-polymerized into polydopamine (PDA).…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[87][88][89][90][91][92][93][94][95][96] Vacuum filtration was used to rapidly self-assemble GO/gellan gum into aligned nacre-like films. The produced films were strong and flexible.…”
Section: Gellan Gum Filmsmentioning
confidence: 99%